DIGITAL MARKETING TRAINING AS AN EFFORT TO ENHANCE THE PROMOTION OF TOURISM VILLAGES IN MOJOKERTO CITY - Ismi Yayuk Rakhmawati; Anita; Rakhmad Wahyudi (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2026)
The development of information technology has shifted the pattern of tourism destination promotion from conventional methods to digital-based marketing. Tourist villages in Mojokerto City possess cultural, culinary, and craft potential that can be developed as tourist attractions, but the use of digital media as a promotional tool is still not optimal. This community service activity aims to improve the ability of tourist village managers to utilize digital marketing as an effective and sustainable promotional medium. The implementation method includes observation, coordination with partners, material development, training, digital content creation practice, and evaluation. The training was attended by tourist village managers. The results showed an increase in participants' understanding of digital marketing concepts, the use of social media for tourism promotion, simple photography and videography techniques, and the creation of engaging promotional content. Participants were also able to create promotional social media accounts and create simple content calendars. This activity has had a positive impact on increasing community capacity in promoting local tourism potential, which is expected to increase tourist visits and support community economic growth.